WebSphere for Linux on iSeries implementation guide - Johng, Yessong (IBM, International Technical Support Organization, 2004)
This IBM Redbooks publication is about WebSphere Application Server V5.0.2 for Linux on iSeries. It begins with a brief discussion of WebSphere Application Server V5.0.2, then provides details about product positioning on the OS/400 versus Linux for iSeries platforms, and about the features included in various packaging options. This book then provides detailed instructions for installing and configuring WebSphere Application Server V5.0.2 for Linux on iSeries. It presents connectivity scenarios between OS/400 resources and Java applications running under WebSphere Application Server V5.0.2 for Linux on iSeries, focused on JDBC provider and program-to-program calling. This information is provided in the context of several realistic business applications. Administration and operation tips and techniques are presented as well. This book helps administrators and developers of WebSphere Application Server V5.0.2 for Linux on iSeries. In addition, it is useful to IT managers or decision makers when considering the pros and cons of the product offerings between OS/400 and Linux on iSeries.
Includes bibliographical references (pages 159-160) and index. - Print version record
Keywords: WebSphere; Linux; Web sites -- Computer programs; Sites Web; Logiciels; Web sites; Computer programs